Analisis Dampak Penggunaan Gadget terhadap Perkembangan Sosial Anak Usia Sekolah Dasar - Atmadianti, Widia; Aziz, Lalu Abdul; Wardani, Trisna Kusuma; Wijaya, Hadi (FONDASI: Jurnal Pendidikan Dasar, 2025)
This study aims to analyze the impact of gadget usage on the social development of elementary school children at SDN Bunklotok. This research employs a qualitative descriptive approach, involving 28 informants, consisting of 22 students, 1 class teacher, and 5 parents. Data collection techniques include participatory observation, interviews, and documentation. Data analysis is performed using the Miles and Huberman technique. The study's results show that most children use gadgets solely for playing games and not for learning or completing school assignments, which negatively affects their social development. The study suggests that parents should be stricter in limiting gadget usage and more involved in interacting with their children at home to optimize their social development.